THE IMPACT OF COVID-19 ON THE ENDOCRINE SYSTEM: AN OVERVIEW - Tillyashaykhova Iroda Mirzagalebovna; Parpiyeva Nargiza Nusratovna; Rakhimova Gulnara Nishanovna (Scholar Express Journals, 2023)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has had far-reaching effects on various physiological systems within the human body. This article provides a comprehensive overview of the impact of COVID19 on the endocrine system, which plays a critical role in regulating hormones and maintaining overall homeostasis. Through a synthesis of current research findings and clinical observations, this article explores the direct and indirect effects of COVID-19 on various components of the endocrine system, including the hypothalamus, pituitary gland, thyroid gland, adrenal glands, and pancreatic islets. Key topics discussed include the potential for viral infiltration of endocrine tissues, dysregulation of hormonal pathways, stress-related responses, and the implications of COVID-19-associated cytokine storms. Additionally, the article addresses the influence of pre-existing endocrine disorders on COVID-19 outcomes and the potential long-term endocrine consequences for survivors. By shedding light on the intricate interplay between COVID-19 and the endocrine system, this overview contributes to a deeper understanding of the pandemic's holistic impact on human health and informs potential avenues for future research and therapeutic interventions
Keywords: COVID-19; SARS-CoV-2; endocrine system